Nagyvárosi régiók fejlesztésének tendenciái a visegrádi országokban - Horváth, Sarolta Noémi (Közép-Európai Közlemények, 2013)
Visegrad Cooperation is a regional organization of Czech Republic, Poland, Hungary and Slovakia. The strategic issues concerning the future of Cohesion Policy as well as the specific questions of the implementation of Structural Fund and Cohesion Fund appear more and more frequently on the political agenda of European Union, hereby in the frame of Visegrad Cooperation, too. The change of direction happening in the cohesion policy of European Union increasingly emphasises the importance of interregional and trans-regional collaboration. The base of the general competitiveness in the countries is that territorial structure should be better balanced and more efficient. The strengthening of territorial cohesion equally means the improvement of regional competitiveness, expansion of employment as well as the territorial closing up and the reduction of regional differences. The goal of the creation of development poles to determine metropolises become such centres what can enhance the international competitiveness of themselves and their wider areas.